All the kit - Hunt, Roderick; Brychta, Alex; Schon, Nick (Oxford : Oxford University Press, 2016)
In All the Kit Kipper gets ready to start school.
An exciting new set of wordless Biff, Chip and Kipper Stories from Roderick Hunt and Alex Brychta. Full of humour and drama with familiar settings and real-life scenarios that children can relate to that will delight young readers. Featuring all your favourite characters, children will enjoy exploring the detailed humorous illustrations and be captivated by the storylines. These wordless stories are perfect for preparing children for their first steps as readers. They are ideal for developing skills in communication and language by encouraging conversation and discussion. Each book contains inside cover notes to help adults read and explore the content with the child, supporting their decoding and language comprehension development. Free teaching notes on Oxford Owl support guided reading, writing, and speaking, listening and drama activities.
Keywords: (Fictitious character from Hunt); Readers (Elementary); Children's stories